LIQUIDUS KARROOITE STABILITY AND COMPOSITION AT REDUCING CONDITIONS - Borisov A.; Brenker F.; Palme H. (My University, 2004)
We have determined the stability of rutile and karrooite on the liquidus of pseudobinary silicate melts of anorthite–diopside eutectic composition with, in addition, of up to 32wt% TiO2 at one atm total pressure and at wide range of oxygen fugacities. At 1,300C and at an fO2 below 10–11.2 atm rutile (TiO2) is replaced as liquidus phase by the pseudobrookite-type MgTi2O5–Ti3O5 solid solution with some Al in the crystal structure. The composition of karrooite was found to be strongly dependent on oxygen fugacity. Crystalline phases were identified by transmission electron microscopy (TEM). The results obtained in this study are relevant for understanding the chemistry of lunar armalcolites. Using excess rutile solubility at reducing conditions, we estimated the Ti4+ /Ti3+ ratio in silicate melts at 1,300C as function of fO2.
Keywords: rutile; karrooite